Manufacturing of Surface Relief Structures in Moving Substrates Using Photoembossing and Pulsed‐Interference Holography. Issue 1 (13th June 2012) - Picot, Olivier T.; Alcalá, Rafael; Sánchez, Carlos; Dai, Mian; Hughes‐Brittain, Nanayaa F.; Broer, Dirk J.; Peijs, Ton; Bastiaansen, Cees W. M.
Abstract Photoembossing is a cost‐effective technique for the production of complex surface relief structures in a photopolymer film, achieved via contact‐mask exposure to UV‐light. Here, photoembossing is explored using interference holography with a CW laser and a nanosecond pulsed laser. It is shown that identical surface relief structures are produced if the photopolymer film is kept in a fixed position. In the case of a moving substrate, relief structures are only obtained with the pulsed laser and the heights of the relief structures and their shape are the same as in the static experiments. This illustrates that photoembossing in combination with pulsed laser interference holography is potentially useful in the production of large area structured films using roll‐to‐roll processes.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>